Assessment of the performance of asphalt rubber layers on noise abatement - Freitas, Elisabete F. (2008)
Layers with a very high content of rubber have shown to be very effective on noise abatement despite their reduced durability. On the contrary, layers with a rubberized asphalt binder have shown to be durable, but their performance regarding noise abatement is not consensual yet. This paper aims at assessing the effect of the use of layers with rubberized asphalt binder on noise abatement. For this purpose seven road sections with different surface types, among which five gap graded and three with rubberized asphalt have been selected. In these road sections the tyre-road noise generated by a heavy truck and two light vehicles at three levels of speed were measured by means of pass-by tests. Surface texture tests were also performed. The results focused on the noise level variation versus speed, the average noise level for each speed level versus type of surface and the average noise level variation with regards to a reference surface. Mixtures with rubberized asphalt did not show a significantly better performance. In fact, the same performance may be achieved with other type of gap graded thin mixtures. The results obtained might be better explained if other parameters than the rubberized asphalt binder are taken into account. Further research on the effect of porosity and texture on noise generation is being done. It is intended to perform absorption tests in all the surfaces analysed in order to study this issue in depth and fully understand the effect of the rubber on noise generation.